"Ruskiy Mir" and "Ukrainskyi Svit": Ontological and Anthropological Antagonists - Fylypovyč, Ljudmyla Oleksandrivna (Occasional papers on religion in Eastern Europe, 2024)
The article focuses on a crucial issue of global interest - attempts of the Russian Federation to reformat the world according to the worldview model of the "Ruskiy mir." The paradigm of the "Ruskiy mir" assumes a system of values (ontological, anthropological, theological, and historiographical ideas and behavioral models) programmed by the entire russian history, as defined by russian culture, traditions, and the russian worldview. According to the "Russian worldview," the world should have a different structure, and the global international system should have a different format: Moscow (the Russian Empire and the Russian Federation) should be at the center of the global world and set the norms for its organization. Armed aggression against Ukraine is the modern stage of such reformatting of the world according to "ruskomirovsky's" models. The Russian Federation also instrumentalizes religion, as it hopes to legitimize a war of aggression through religious interpretation implanted in the minds of believers. Religion is turning into an instrument of sacralization of the war of occupation and a means of controlling the consciousness of Russians. For this purpose, the war is declared holy, and the meaning and evaluation of events are changed to their opposites: from "occupation of the territory of Ukraine" to "liberation of Holy Russia." They also legalize murder, robbery, and other war crimes committed by anyone who supposedly fulfills their "sacred duty." These rationalizations are seen as completely logical by the "Russian worldview," and the war of aggression to destroy Ukrainians is equally justified. After all, according to their ideas, 1) Ukrainians do not exist as a nation; they are "wrong Russians," and 2) Ukraine as an independent state does not exist; they are an occupied territory by "wrong Russians." These ideas, which motivate Russians to kill Ukrainians, stem from an artificially formed false historiographical legend, according to which "Russians" are the true descendants of the ancient Rus, and therefore have a special civilizing mission, which is embodied by the expansive policy of Moscow/Russian Empire/Soviet Union/Russian federation. Such a paradigm is based on specific worldview foundations: ideas about people, about relationships between people, about the world structure, about the proper way of organizing the world, and about effective methods of its correction. These parameters of the Russian worldview are opposed to the worldview foundations of Ukrainians. Ideas about the world, people, relationships and standards of life of Ukrainians and Russians are mostly mutually exclusive. That is why Ukrainians are